In vitro antioxidant potential of the essential oil and leaf extracts of Curcuma zedoaria Rosc. - Atiqur Rahman, Monira Afroz, Rafiquel Islam, Kazi Didarul Islam, M. Amzad Hossain and Minkyun Na (Journal of Applied Pharmaceutical Science, 2014)
In this study, we examined the chemical composition of the essential oil and tested the antioxidant potential of the oil and leaf extracts of Curcuma zedoaria Rosc. The chemical compositions of the oil were analysed by GC-MS. Twenty-four compounds representing 92.4% of the total oil was identified. The antioxidative potential was evaluated using two separate methods, inhibition of free radical 1, 1-diphenyl-2-picrylhydrazyl (DPPH) and superoxide radicals scavenging activities assay. In the first case, the IC50 value of the oil was 14.8 ± 2.2. Among the extracts, the strongest activity was exhibited by the ethyl acetate extract (IC50 = 17.56 ± 1.6 µg/ml). In the superoxide radicals scavenging activities assay, ethyl acetate extract was superior to all other extracts (IC50 = 23.47 ± 1.2 µg/ml). Furthermore, the amount of total phenolic compounds was also determined as gallic acid equivalent. Thus, the natural products produced from C. zedoaria may be used in food and pharmaceutical industries.
Keywords: Curcuma zedoaria Rosc, essential oil,GC-MS,antioxidant activities, total phenolics.